The Dysfunction of Innovation: Competency Barriers and Procedural Bureaucracy in Central Java’s Religious Affairs Office Revitalization - Nur Laela (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The urgency of transitioning the role of the Office of Religious Affairs in Central Java is currently hindered by the disparity between the grandeur of physical infrastructure resulting from revitalization and the quality of personnel performance, which remains trapped in a traditional administrative mindset. The core issue lies in the absence of an innovation incentive system, leading to a rigid and change-resistant procedural organizational culture. The policy methodology applied in this paper utilizes a qualitative descriptive approach within William N. Dunn’s evaluation framework. Data collection was conducted through an in-depth review of sectoral performance reports, public service regulations, and observations of organizational dynamics at the grassroots level. Analysis results indicate that the lack of incentives for change agents causes low adoption of non-marriage services and widens the digital competency gap within the work environment. In the discussion, it is found that without re-engineering a merit-based career system, personnel will continue to act pragmatically and avoid innovation risks for the sake of mere administrative security. Therefore, a comprehensive policy scheme is recommended that integrates innovation rewards with mandatory public communication competency certification programs. Consistent implementation of these recommendations will shift the institutional identity from a mere document recording unit to a multidimensional and responsive religious solution center. Such strategic steps are the primary keys to ensuring that physical investment aligns with tangible public satisfaction, while simultaneously breaking the shackles of bureaucratic pathology that have long hindered the acceleration of institutional revitalization functions amidst modern societal demands.